Hydrolysis of coffee pulp as raw material for bioethanol production: sulfuric acid variations - Mawaddah, Mawaddah; Setiawan, Adi; Zulnazri, Zulnazri; Putri, Almia Permata; Khan, Naseer A.; Jain, Vishal (Institute for Research and Community Service, Universitas Malikussaleh, Indonesia, 2022)
Indonesia has enormous biomass resources due to its land territory is mostly surrounded by forests and agricultural area. One of the main agricultural commodities is Gayo Arabica coffee. Coffee agro-residue such as coffee-pulp contains glucose, organic matter, protein, nitrogen and high minerals. Therefore, coffee pulp can be a potential raw material for bioethanol production. In order to develop an effective technology for bioethanol production from coffee-pulp, it is necessary to investigate in early the way of glucose can be effectively prepared. In this preliminary investigation, glucose products ware prepared using two methods, i.e. method-I under several main-stages including extraction, delignification, and hydrolysis. While, under method-II, the sample was directly hydrolyzed at 100Â°C for 4 h. Under both methods, hydrolysis process to get glucose was performed by adding sulfuric acid (H2SO4) at various concentrations (8 wt.%, 10 wt.% and 12 wt.%). Based on analysis results, the highest glucose level, i.e. 17 % was obtained from method-II by adding 8 wt.% sulfuric acid. The less the amount of sulfuric acid added, the higher the glucose level produced. No difference in pH was found from both methods. The color of glucose produced under method-I is clearer compared to those prepared under method-II.